An anaplerotic approach to correct the mitochondrial dysfunction in ataxia-telangiectasia (A-T) - A.J. Yeo; G.N. Subramanian; K.L. Chong; M. Gatei; R.G. Parton; D. Coman; M.F. Lavin (Elsevier, 2021)
Background: ATM, the protein defective in the human genetic disorder, ataxia-telangiectasia (A-T) plays a central role in response to DNA double-strand breaks (DSBs) and in protecting the cell against oxidative stress. We showed that A-T cells are hypersensitive to metabolic stress which can be accounted for by a failure to exhibit efficient endoplasmic reticulum (ER)-mitochondrial signalling and Ca2+ transfer in response to nutrient deprivation resulting in mitochondrial dysfunction. The objective of the current study is to use an anaplerotic approach using the fatty acid, heptanoate (C7), a metabolic product of the triglyceride, triheptanoin to correct the defect in ER-mitochondrial signalling and enhance cell survival of A-T cells in response to metabolic stress. Methods: We treated control cells and A-T cells with the anaplerotic agent, heptanoate to determine their sensitivity to metabolic stress induced by inhibition of glycolysis with 2- deoxyglucose (2DG) using live-cell imaging to monitor cell survival for 72 h using the Incucyte system. We examined ER-mitochondrial signalling in A-T cells exposed to metabolic stress using a suite of techniques including immunofluorescence staining of Grp75, ER-mitochondrial Ca2+ channel, the VAPB-PTPIP51 ER-mitochondrial tether complexes as well as proximity ligation assays between Grp75-IP3R1 and VAPB1-PTPIP51 to establish a functional interaction between ER and mitochondria. Finally, we also performed metabolomic analysis using LC-MS/MS assay to determine altered levels of TCA intermediates A-T cells compared to healthy control cells. Results: We demonstrate that heptanoate corrects all aspects of the defective ER-mitochondrial signalling observed in A-T cells. Heptanoate enhances ER-mitochondrial contacts; increases the flow of calcium from the ER to the mitochondrion; restores normal mitochondrial function and mitophagy and increases the resistance of ATM-deficient cells and cells from A-T patients to metabolic stress-induced killing. The defect in mitochondrial function in ATM-deficient cells was accompanied by more reliance on aerobic glycolysis as shown by increased lactate dehydrogenase A (LDHA), accumulation of lactate, and reduced levels of both acetyl CoA and ATP which are all restored by heptanoate. Conclusions: We conclude that heptanoate corrects metabolic stress in A-T cells by restoring ER-mitochondria signalling and mitochondrial function and suggest that the parent compound, triheptanoin, has immense potential as a novel therapeutic agent for patients with A-T.